Atomic Layer Deposition의 두께 변화에 따른 NCM 양극에서의 고전압 리튬 이온 전지의 전기화학적 특성 평가 - 임진솔; 안진혁; 김정민; 성시준; 조국영; Im, Jinsol; Ahn, Jinhyeok; Kim, Jungmin; Sung, Shi-Joon; Cho, Kuk Young (전기화학회지, 2019)
High-voltage operation of the lithium ion battery is one of the advantageous approaches to obtain high energy capacity without changing the conventional cell components and structure. However, operating at harsh condition inevitably results in severe side reactions at the electrode surface and structural disintegration of active material particles. Herein we coated layers composed of $Al_2O_3$ and ZnO on the electrode based on NCM using atomic layer deposition (ALD). Thicker layers of novel Al-doped ZnO (AZO) coating compared to conventional ALD coated layers are prepared. Cathode based on NCM with the varying AZO coating thickness are fabricated and used for coin cell assembly. Effect of ALD coating thickness on the charge-discharge cycle behavior obtained at high-voltage operation was investigated. 이차 전지의 고전압 구동은 기존 셀 구조의 변화 없이도 고용량을 구현할 수 있는 유용한 접근 방법 중에 하나이나, 전극 표면에서의 극심한 부반응과 전극 활물질의 구조 붕괴 등과 같은 문제를 야기하게 된다. 본 연구에서는 니켈-망간-코발트 삼성분계(NCM) 활물질을 도입한 양극의 고전압 구동을 위해 원자층 증착법 (Atomic Layer Deposition, ALD)을 통해 전극판 표면에 $Al_2O_3$와 ZnO층으로 구성된 코팅 층을 형성하였다. 기존 ALD법으로 제조되는 박막에 비해 유사한 조건에서도 두꺼운 Al-doped ZnO (AZO)층을 최초로 형성하였고, 코팅된 AZO층의 두께를 달리한 NCM 기반의 양극판을 제조하였다. ALD 코팅된 양극이 도입된 코인셀을 제조하여 두껍게 형성된 코팅 층의 두께에 따른 고전압에서 충방전 거동을 확인하였다.